Improving the Efficiency of Thin Film Thermoelectric Generators under Constant Heat Flux by Using Substrates of Low Thermal Conductivity. Issue 10 (22nd August 2018) - Morales, Carlos; Flores, Eduardo; Ares, José R.; Sánchez, Carlos; Ferrer, Isabel J.
Abstract : Thin film thermoelectric generators performance needs to be improved to be competitive with their bulk counterpartners. Here, a method has been proposed to enhance the efficiency of non‐conventional thin film thermoelectric generators, i.e., those with heat running parallel to the film surface, under constant heat flux configuration. This geometry offers the possibility to decouple the thermal and electronic transport via an adequate selection of the film and substrate thermal conductivities and their respective thicknesses. An analysis of those parameters and their relationships in order to reach the maximum thin film thermoelectric generators efficiency is presented in this work. It has been concluded that under well‐established conditions, the thin film thermoelectric generators efficiency is clearly increased and becomes comparable to that of the bulk thermoelectric generators under constant heat flux. This novel framework can lead to the use of devices based on compounds with high power factor regardless of their thermal conductivity. Abstract : Efficiency enhancement of non‐conventional thin film thermoelectric generators is done by an adequate selection of film and substrate thermal conductivities and thicknesses. The effective decoupling of thermal and electronic transport allows the use of compounds with high power factor regardless of their thermal conductivity.